Construction of a human topological model from medical data. - Magnenat-Thalmann, N. (IEEE Transactions on information technology in biomedicine)
Medical imaging can provide data for useful views of the interior details of human anatomy. In addition to visualization, which in general has been the primary reason for obtaining these data, many other uses are possible. These include modeling of different elements and their inter-relationships -topological modeling, simulation of physical processes, analysis of movements and validation of models. In this paper, we describe some of the modeling issues from medical imaging. The issues are particularly related to topological modeling of different anatomical elements: bones, muscles, articulations, etc. A 3D topological modeler is presented with which anatomists and other users can build a topological database containing structural, topological and mechanical information of anatomical elements.